Incidence of Major Adverse Cardiovascular Events in Patients With Rheumatoid Arthritis Treated With JAK Inhibitors Compared With Biologic Disease-Modifying Antirheumatic Drugs: Data From an International Collaboration of Registries - Aymon, Romain; Mongin, Denis; Guemara, Romain; Salis, Zubeyir; Askling, Johan; Choquette, Denis; Codreanu, Catalin; Di Giuseppe, Daniela; Flouri, Irini; Huschek, Doreen; Hyrich, Kimme L; Iannone, Florenzo; et al. (Arthritis & rheumatology (Hoboken, N.J.), 2025)
OBJECTIVE: Our objective was to assess the incidence of major adverse cardiovascular events (MACEs) in patients with rheumatoid arthritis (RA) treated with JAK inhibitors (JAKi), tumor necrosis factor inhibitors (TNFi), or biologic disease-modifying antirheumatic drugs with other modes of action (bDMARD-OMA) in a multicountry, real-world population. METHODS: Patients with RA from 15 registries in the JAK-pot collaboration were included. MACE incidence was analyzed using two approaches: a within-registry analysis aggregating country-specific estimates from registers with >25 incident MACEs through meta-analysis and an individual-level data combined analysis. We used adjusted linear mixed Poisson regression to obtain incidence rate ratios (IRRs) of MACEs between treatment groups, accounting for multiple treatment courses. RESULTS: The study included 73,008 treatment courses (16,417 JAKi, 35,373 TNFi, and 21,218 bDMARD-OMA) and 828 incident MACEs among 51,233 patients. Median follow-up time was 1.3 years, with most of the follow-up concentrated in the first two years of treatment. Incidence rates were 7.0, 7.6, and 11.8 per 1,000 person-years for JAKi, TNFi, and bDMARD-OMA, respectively. Compared to TNFi, JAKi (within-registry adjusted IRR 0.89, 95% confidence interval [CI] 0.63-1.25) had similar incidence rates of MACEs and bDMARD-OMA had higher rates (within-registry adjusted IRR 1.35, 95% CI 1.10-1.66). Combined analysis showed similar results. CONCLUSION: Observational data from the JAK-pot collaboration show no evidence of an increase in cardiovascular events during the first two years of use with JAKi compared to TNFi in the general RA population.
Keywords: Male; lidé středního věku; revmatoidní artritida; Humans; Middle Aged; senioři; Cardiovascular Diseases; kardiovaskulární nemoci; mužské pohlaví; Female; inhibitory TNF; Aged; inhibitory Janus kinas; antirevmatika; biologické přípravky; Antirheumatic Agents; Registries; ženské pohlaví; incidence; Incidence; registrace; Adult; Janus Kinase Inhibitors; lidé; dospělí; Biological Products; Tumor Necrosis Factor Inhibitors; Arthritis, Rheumatoid